Implementasi Watermarking pada Citra Digital dengan Metode Singular Value Decomposition (svd) - Aah Sumiah; Yan Alfian (JEJARING : Jurnal Teknologi dan Manajemen Informatika, 2021)
Today computers have been used in all aspects of life as a means of processing digital data. The Development of computer makes digital files mostly used because the computer is an electronic equipment used to process digital file. Moreover with network technology developments internet it enables file exchange and process the file.This ease impacts to copyright, so that needs to be considered the protection of copyrights. Such protection insertion namely with a proprietary identity against certain files.one of them is watermarking technique. There are several techniques of digital watermarking which have developed. One technique is digital watermark image on singular value decomposition (svd), ie insertion a singular image. Watermarking method using singular value decomposition (svd) leads the overall in scattered watermark image, so that when the slightest changes occurred on with easy image can be known. In addition itu resistant against different attacks, such as croping, rotation changes. The author discusses about the digital image watermarking based svd. In making application he uses delphi 7.Keywords: Digital Image, Watermarking, Singular Value Decomposition.